Shedding Light on Voluntary Forward-Looking Information Disclosure: An International Comprehensive Literature Review - Almhuob Muftah, Imad H.; Yuserrie, Zainuddin (Human Resource Management Academic Research Society (HRMARS), 2023)
The current study aims to review the global body of literature concerning Forward-Looking Information Disclosure (FLID). Previous studies on FLID were categorised and evaluated based on five distinct themes: antecedents, measurements, determinants, characteristics, and consequences. Within this investigation, we have recognised methodological concerns, prospects for future research, and implications. The highlighted concerns pertain to the measurements of FLID and the empirical models used in prior studies. Our review uncovers several areas that warrant further investigation. The present study contributes valuable insights to the accounting literature. These insights hold potential implications for researchers, investors, managers, regulatory bodies, and policymakers, as they can aid in improving information quality and promoting greater transparency in annual report narratives.